DRY MATTER AND NUTRIENT UPTAKE OF RABI MAIZE AS INFLUENCED BY DRIP FERTIGATION OF NITROGEN, POTASSIUM AND MICROBIAL CONSORTIUM - S.TRIVENI, A.SAI KIRAN, K.AVIL KUMAR, M. UMA DEVI, B. BALAJI NAIK and (The Journal of Research, PJTSAU, 2020)
Maize is the third most important food crop next to rice and wheat and is not only grown for food and fodder but also for several industrial usage and acquired dominant role in the farming sector and macroeconomy of the Asian region (Mauria et al., 1998). Water and fertilizers are important production factors for improving maize production and drip fertigation assures an effective and economical way to supply water and nutrients for the crops. Biofertilizers can partially replace chemical fertilizers. Biofertilizers are gaining importance as they are ecofriendly, nonhazardous and non-toxic products. The biofertigation, that is application of liquid biofertilizers or microbial consortium along with drip irrigation can precisely deliver the bioinoculants in the root zone. The present study was planned to evaluate the performance of biofertigation under field condition along with fertigation of inorganic fertilizers on rabi maize.